The effect of climbing and descending stairs varies in improving balestra fencing floret/foil weapon type - Amahoru, Musfira; Mahyudin, Reza; Samudro, Touvan; Dahlan, Firmansyah; Idha, Takbiratul (Universitas Negeri Yogyakarta, 2023)
Fencing is a sport that requires a maximum physical component so that in this study the aim was to test and find out the effect of variations in stair climbing exercises in improving floret/foil balestra fencing weapons. This study used a test-experiment with the research design